Admissibility of Compensation for Moral Harm as a Consequence of a Tort Committed During the Soviet Era - S. S. Borja (Теоретическая и прикладная юриспруденция)
The article substantiates the invalidity of the position formed in the Russian judicial practice about inadmissibility of compensation for physical and moral suffering caused to citizens as a result of offenses committed during the period of the Civil Codes of the Russian Soviet Federative Socialist Republic of 1922 and 1964. For this purpose, the author turns to the discussion of Soviet jurists on the admissibility of recovery of moral damages and evaluates the arguments of the parties for compliance with positive law. As a result, it is concluded that the inadmissibility of material compensation for non-pecuniary harm at that time was conditioned by arguments of a purely ideological nature and that there were no formal obstacles in Soviet civil legislation to the fi ling and satisfaction of such claims, which could be based on the rule of the general tort.